Thermal Effect and Frequency Response Analyses on Heterojunction Bipolar Power Transistor - K. F. Yarn; K. H. Ho (Active and Passive Electronic Components)
Heterojunction bipolar transistors (HBT) based on Npn AlGaAs/GaAs material system have attracted considerable attention for microwave power and digital applications due to their high speed and high current capabilities. In this paper, a numerical model based on the Npn AlGaAs/GaAs HBT structure for the carrier transport is presented. Three figures of merit on device operation, current gain, cut-off frequency and maximum oscillation frequency are calculated. Besides, thermal instability plays an important role on power HBT resulted from the low thermal conductivity in GaAs. The generated heat will increase the junction temperature and cause self-destruction. Therefore, the thermal runaway study of the junction temperature, current–voltage (IV) characteristics and frequency response using an analytical thermal model is described.